Multiply both sides of the equation by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Simplify the left side.

Simplify <math><mstyle displaystyle="true"><mn>4</mn><mrow><mo>(</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>4</mn></mrow></mfrac><mo>⋅</mo><mrow><mo>(</mo><mi>x</mi><mo>+</mo><mfrac><mrow><mn>3</mn></mrow><mrow><mn>5</mn></mrow></mfrac><mo>)</mo></mrow><mo>)</mo></mrow></mstyle></math> .

Apply the distributive property.

Combine <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>4</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>4</mn></mrow></mfrac><mo>⋅</mo><mfrac><mrow><mn>3</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>4</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Apply the distributive property.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>20</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Simplify the right side.

Multiply <math><mstyle displaystyle="true"><mn>4</mn><mrow><mo>(</mo><mfrac><mrow><mn>2</mn></mrow><mrow><mn>5</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>2</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> from both sides of the equation.

Combine the numerators over the common denominator.

Subtract <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> .

Divide <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Do you know how to Solve for x 1/4(x+3/5)=2/5? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.